Joachimus Hoppe Civitatis Gedanens. Prae-Consul Montanorumq Administ. / W. C. Maier. - Maier, Wolfgang Christoph (czynny 1746-1772) (1746)
Przedstawia portret w popiersiu gdańszczanina Joachim Hoppe (1656-1712), burmistrza Gdańska.